Anti-Korupsi dalam Pendidikan Islam (Studi tentang Implementasi Nilai-Nilai Integritas dalam Sistem Pendidikan) - M. Khairul Amri (Departement of Mathematics Education, 2023)
Corruption is a problem that is of global concern and is a problem that results in great losses for the state and society. Although in every country has different cases of corruption. In the field of education, corruption can have an impact on the quality of education and reduce public trust in the education system. Islamic education has integrity values that can be a solution in overcoming the problem of corruption. This type of research is literature or literature research and is descriptive exploratory in nature. The focus of the discussion in this method is an attempt to describe, discuss and explore the main ideas which are then drawn conclusions and do not rule out the possibility that new cases will emerge. The results of the research show that the implementation of integrity values in Islamic education has a positive impact on the education system. Values such as honesty, fairness and responsibility help create a good school climate and build people's trust in the education system. Implementation of integrity values also helps reduce acts of corruption in the education system. The implementation of integrity values in Islamic education has a positive impact on the education system and can be a solution to overcome the problem of corruption in education. Therefore, efforts are needed to implement the values of integrity in the education system widely.